Factors affecting the meat quality parameters of clarias gariepinus (Burchell) - Hoffman, Louwrens Christiaan (My University, 1995)
Refer to document
Thesis (Ph.D. Physiology)) -- University of Limpopo, 1995
Keywords: Fish meat quality; Meat -- Quality; Clarias; Burchell family